2018
DOI: 10.1542/pir.2017-0249
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cervical Lymphadenopathy

Abstract: Cervical lymphadenopathy affects as many as 90% of children aged 4 to 8 years. With so many children presenting to doctors' offices and emergency departments, a systematic approach to diagnosis and evaluation must be considered. In the following review, we aim to provide the pediatric clinician with a general framework for an appropriate history and physical examination, while giving guidance on initial diagnostic laboratory testing, imaging, and potential need for biopsy. The most common cause of cervical lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 26 publications
0
39
0
11
Order By: Relevance
“…Ultrasonography can be used to further delineate the nature of the lymph node. Patients who continue to have persistent symptoms for more than 4–6 weeks despite appropriate therapies may require an excisional biopsy 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography can be used to further delineate the nature of the lymph node. Patients who continue to have persistent symptoms for more than 4–6 weeks despite appropriate therapies may require an excisional biopsy 13…”
Section: Discussionmentioning
confidence: 99%
“…Lymphadenopathy can also be caused by bacteria (acute bacterial lymphadenitis), fungi and parasites. Less frequently, there are other non-infectious causes, such as malignancies, metastasis and some specific diseases 13. An enlarged lymph node in the supraclavicular location is a rarer and more worrisome finding suggesting either primary lymphatic malignancy, infection in the mediastinum or a metastatic malignancy from the abdomen 14…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Although our study did not standardize the collection of ultrasound measurements and architecture, we did note that ultrasound findings were often concordant with final pathology; together these data support that ultrasonography remains a useful, low-risk option to help risk-stratify patients with cervical lymphadenopathy. Using ultrasound for assistance with diagnosis remains an area of interest [14], with many studies suggesting it as first-line imaging for pediatric lymphadenopathy [15]. Niedzieleska et al demonstrated that abnormal shape of a lymph node and/or hilum or abnormal intranodal vascularization on ultrasound suggests etiologies besides benign/reactive lymphadenopathy and warrant further investigation [16].…”
Section: Discussionmentioning
confidence: 99%
“…Enlargement usually occurs inside the cortex, so the hypoechoic peripheral ring is thicker in inflammatory lymph nodes . Vascularity can appear increased . Blurred margins, a round shape, loss of central echogenicity and presence of structural changes such as cortical nodules, intranodal necrosis or reticulation or matting, are all well‐known criteria that suggest malignancy .…”
Section: Ultrasonographic Findings Of Inflammatory Dermatosesmentioning
confidence: 99%
“…Blurred margins, a round shape, loss of central echogenicity and presence of structural changes such as cortical nodules, intranodal necrosis or reticulation or matting, are all well‐known criteria that suggest malignancy . In color Doppler mode, peripheral, mixed (peripheral and central), or chaotic vascularity are criteria that suggest malignant invasion . However, these features may also be seen in tuberculosis (Figure ), Kimura disease and Rosai‐Dorfman disease .…”
Section: Ultrasonographic Findings Of Inflammatory Dermatosesmentioning
confidence: 99%